3^2x^2-2.3x^2+x+6+3^[x+6]=0
Answers
Answered by
13
Answer:
(3^x^2)^2–2•3^x^2•3^(x+6)+3^2(x+6)=0
Let 3^x^2=Y
Now,y^2–2•3^(x+6)•y+3^2(x+6)=0
y^2–2•3^(x+6)•y+{3^(x+6)}^2=0
{Y-3^(x+6)}^2=0
Y-3^(x+6)=0
3^x^2-3^(x+6)=0
3^x(3^(x^2-x)-3^6)=0
3^(x^2-x)-3^6=0
3^(x^2-x)=3^6
X^2-X-6=0
X=3,-2
Answered by
13
SOLUTION
Refer to the attachment
hope it helps ☺️
Attachments:
![](https://hi-static.z-dn.net/files/d46/ba5449ffe7f446fad828971f62604c81.jpg)
Similar questions
Math,
7 months ago
Computer Science,
7 months ago
Biology,
1 year ago
Math,
1 year ago
English,
1 year ago